2021
DOI: 10.1177/00380407211013322
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the Logic of Compliance in Special Education: Contextual Influences on Discipline Racial Disparities in Suburban Schools

Abstract: The Individuals with Disabilities Education Act ([IDEA] 2004; IDEA Amendments 1997) is a civil rights–based law designed to protect the rights of students with disabilities in U.S. schools. However, decades after the initial passage of IDEA, racial inequity in special education classifications, placements, and suspensions are evident. In this article, we focus on understanding how racial discipline disparities in special education outcomes relate to IDEA remedies designed to address problem behaviors. We quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 30 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…Descriptive analyses also revealed that cited suburban districts were more racially and linguistically diverse, had higher poverty rates, and lower levels of achievement compared to suburban districts that were never cited (see Kramarczuk Voulgarides et al, 2021). In addition, suburban districts with three or more citations enrolled the highest number of students of color and suspension rates in these districts were more than three times greater than districts that were never cited.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Descriptive analyses also revealed that cited suburban districts were more racially and linguistically diverse, had higher poverty rates, and lower levels of achievement compared to suburban districts that were never cited (see Kramarczuk Voulgarides et al, 2021). In addition, suburban districts with three or more citations enrolled the highest number of students of color and suspension rates in these districts were more than three times greater than districts that were never cited.…”
Section: Methodsmentioning
confidence: 98%
“…The state determined significant disproportionality by using a risk index and relative risk ratio (see Kramarczuk Voulgarides et al, 2021). The state could cite a school district through either measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compliance logic treats district and school administrators as playing roles in structuring and monitoring meetings as well as in analyzing data on programs and outcomes (Voulgarides, 2018(Voulgarides, , 2021. Voulgarides (2021) offered insights on how the compliance logic defines SpEd implementation activities as bureaucratic work. There exist weighty administrative burdens associated with the compliance model of SpEd (Klein, 2004;Moynihan et al, 2015).…”
Section: Compliancementioning
confidence: 99%
“…These constraints tie to several deeply institutionalized aspects of SpEd, including: regulations on credentials for special versus general education teachers, using legal language in IEP meetings, and paperwork tracking minutes of services (Bray & Russell, 2018 ). Rather than justly serving students and families, many taken-for-granted aspects of SpEd reinforce ableism and racism (Annamma et al, 2013 ; Voulgarides et al, 2021 ). To elucidate how to disrupt aspects of SpEd—and implement equity-oriented SpEd—we apply the institutional logics perspective.…”
Section: Purposementioning
confidence: 99%